Psoriasiform syphilis associated with human immunodeficiency virus/AIDS. A case presentation - Julio Cesar Camero Machin; Roxana Rivera Rivadulla; Grecia María Giniebra Marín (Medisur)
Syphilis and human immunodeficiency virus infection are sexually transmitted diseases that affect groups with similar risk practices, so coinfection is common. The clinical case of a male patient with a positive diagnosis of human immunodeficiency virus, 38 years old, heterosexual, attended in the Dermatology consultation, due to the presence of multiple psoriasiform lesions located in the left gluteal region, asymptomatic, sudden onset, accompanied by fever of 38˚C and general manifestations is presented. Laboratory tests made it possible to diagnose atypical secondary syphilis and rule out other sexually transmitted infections. The histopathological examination excluded other erythematosquamous dermatoses, it had conclusive weight in this case. The increase in the incidence of this entity associated with the human immunodeficiency virus/AIDS, the atypical manifestations in seropositive patients and its impact on the life quality of these patients motivated the presentation of this clinical case.